Rancang Bangun Aplikasi Monitoring Dan Safety Fasilitas Regulator Sektor Induk Pada PD. Petro Berbasis Web - Amrie Muharam; Fajriyah Fajriyah; Phinton Panglipur (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
PD. Petro is one of the government institutions located under the auspices of the Prabumulih City Government. How to record monitoring reports at this institution is still using the manual method which causes frequent errors, resulting in inaccurate data. In addition, the manual method must go through a long process and requires a relatively long time, as well as less secure data storage. The purpose of this research is to build an application website to make it easier for PDs. Petro is in the process of recording monitoring reports because they are well computerized and easy to use. The research method uses a qualitative descriptive method with data collection in the form of observation, interviews and literature study. The type of data consists of qualitative data and the source data consists of primary and secondary data. The device development method uses the prototype method. System design tools used are use case diagrams, class diagrams and activity diagrams. This application was built using a website with the PHP programming language and MySQL database.